Is the Transrectal Diameter (TRD) Suitable for Assessing Faecal Loads and Monitoring Bowel Management in Children with Hirschsprung Disease-ReKiSo Study: Prospective Study - Judith Lindert; Daniel Erkel; Felix Schulze; Meike Hofer; Edyta Rzepka; Stefanie Märzheuser (MDPI AG, 2024)
Background: Constipation and outlet obstruction may persist after successful pull-through in Hirschsprung Disease (HD). The radiographic assessment of the faecal load is widely used but exposes the child to radiation. This study aims to evaluate whether the transrectal diameter (TRD) assessed with ultrasound correlates with symptoms of faecal load and whether the TRD normalises when symptoms disappear. Method: Children with HD after pullthrough and functional constipation presenting to our colorectal clinic between 4/23 and 4/24 were assessed for symptoms of constipation, smearing and outlet obstruction, as well as healthy controls. Ultrasound measurement of the TRD was conducted. Bowel management was initiated according to our institutional pathway using Peristeen© irrigation after an orthograde disimpaction regime. Results: A total of 193 children underwent TRD assessment. Of 60 children with HD, 26 (43.3%) presented with obstructive symptoms, and 34 (56.7%) were asymptomatic. In asymptomatic patients with HD, the mean TRD of 2.26 cm (SD 0.61) was significantly (p < 0.001) lower than in HD with symptoms, with a mean TRD of 3.35 cm (SD 1.03). Individuals without colorectal pathology had a mean TRD of 2.04 cm (SD 0.37), and children with functional constipation and symptoms showed a mean TRD of 4.36 cm (SD 1.32). The mean TRD after symptom resolution was 2.37 cm. Conclusions: Children with HD without obstructive symptoms have a TRD < 3 cm, as do controls. The transrectal diameter allows the clinician to sonographically assess the faecal load in children with HD at the bedside without radiation. The TRD is useful for monitoring a bowel management program in children with HD.